Muhāribah in Shia Jurisprudence, Iranian Law and Islamic Schools of Thought - Rasoul Rabani Ki (پژوهش‌های فقهی مسائل مستحدثه)
Received: 2023 Apr 12  |   Recieved in revised form: 2023 Jul 5   |   Accepted: 2023 May 8   |   Published: 2023 Oct 23In Shia Jurisprudence, Iranian Law, and various Islamic Schools of Thought, there is a debate regarding the relationship between Ifsād fi al-Ardh (corruption on the Earth) and Muhāribah. While some jurists consider these two to be a single crime, others argue that Ifsād fi al-Ardh is an independent criminal offense separate from Muhāribah. The basis for this viewpoint can be found in various sources, including verses 32 and 33 of Surah Ma'idah, which address sedition, a section of the Qāsi'ah Sermon, the narration of Fazl bin Shāzān, the narration of Ibn Ubayd, evidences related to the Amr bi al-Marūf wa Nahy az Munkar (promotion of virtue and prevention of vice), and evidence pertaining to Ta'zīrī crimes (discretionary punishable crimes). Additionally, there are narrations in different chapters of Islamic jurisprudence that discuss the concept of the Mufsid fi al-Ardh (corrupter on the Earth), further supporting the perspective of this group of jurists. Muhāribah is defined as cutting off the road, which includes acts such as stealing people's property in passes and roads outside the city and residences. This definition aligns Muhāribah more closely with theft, and it is less commonly found in the teachings of Imamiyyah jurists. Instead, it is predominantly documented in the views of Ahl al-Sunnah, who state that "Harābah means cutting off the path or stealing a large amount." It is argued that if we consider a corrupt person as the subject of a specific punishment, then according to the honorable aforementioned verses, such a ruling cannot be applied, as the mention of Muhāribah would need to be canceled. This explanation suggests that when two things are subject to different rulings, one being absolute (mutlaq) and the other being conditional (muqayad), the falsification of the specific ruling automatically cancels it. To avoid this contradiction, the absolute ruling must take precedence over the conditional one. In this case, if there is a construction, both the ruling for Muhārib corruptor and the ruling for absolute corruptor are the same, making it Muhāribah. This verse implies that legitimate killing is only permissible in two cases: executing qisās (retaliation) and combating Muhāribah (corruption on the Earth).Rabani Kia, R. (2023) Muhāribah in Shia Jurisprudence, Iranian Law and Islamic Schools of Thought. Quarterly of New Perspectives in Islamic Jurisprudence, 1 (1) 257-282. Doi: https://doi.org/10.22091/RCJL.2023.9471.1024.